Comparing Time Efficiency of Sprint vs. High-Intensity Interval Training in Reducing Abdominal Visceral Fat in Obese Young Women: A Randomized, Controlled Trial - Tong, Tomas K.; Zhang, Haifeng; Shi, Hongru; Liu, Yang; Ai, Jingwen; Nie, Jinlei; Kong, Zhaowei (Frontiers in Physiology, 2018)
Introduction: High-intensity interval training (HIIT) is an emerging lifestyle intervention strategy for controlling obesity. HIIT consisted of brief all-out supramaximal sprint intervals was termed as sprint interval training (SIT). This study was designed to examine the time-efficient characteristics of SIT in reducing abdominal visceral fat. Methods: A randomized controlled trial was conducted to compare the specific adaptations of SIT (80 × 6 s all-out cycle sprints interspersed with 9 s passive recovery) with those resulting from a HIIT regimen with training volume relatively higher (repeated 4 min bouts of cycling at 90% V˙O2max alternated with 3 min rest, until the work of 400KJ was achieved), and with those of nonexercising control counterparts (CON). Forty-six obese young women (body fat percentage ≥30) received either SIT (n = 16), HIIT (n = 16), or no training (n = 14), 3–4 sessions per week, for 12 weeks. The abdominal visceral fat area (AVFA) and abdominal subcutaneous fat area (ASFA) of the participants were measured through computed tomography scans pre-intervention and post-intervention. Total fat mass and the fat mass of the android, gynoid, and trunk regions were assessed through dual-energy X-ray absorptiometry. Results: Following the intervention, abdominal visceral and subcutaneous fat were reduced markedly (p < 0.05). The reduction in AVFA (−6.31, −9.7 cm2) was not different between SIT and HIIT (p > 0.05), while the reduction in ASFA (−17.4, −40.7 cm2) in SIT was less than that in HIIT (p < 0.05). Less reduction in the fat mass of the trunk (−1.2, −2.0 kg) region was also found in SIT, while the reductions in fat percentage (−1.9%, −2.0%), total fat mass (−2.0, −2.8 kg), and fat mass of the android (−0.2, −0.2 kg), and gynoid (−0.4, −0.3 kg) regions did not differ between the two regimes (p > 0.05). In contrast, the increase in V˙O2max was significant greater following the SIT than HIIT (p < 0.01). No variable changed in CON. Conclusion: Such findings suggest that the lower training load and exercise time commitments of the SIT regime could optimize the time-efficiency advantage of the traditional HIIT, facilitating the abdominal visceral fat reduction in obese young women.